Genesis endapan aluvium Dataran Purworejo Jawa Tengah; Implikasinya terhadap sumber daya geologi - Bronto, Sutikno (Geological Agency, 2007)
http://dx.doi.org/10.17014/ijog.vol2no4.20072Purworejo is part of the Southern Central Jawa alluvial plain that is bordered by the South Sera- yu Mountains and Sumbing Volcano in the north, West Progo Mountains in the east, Indian Ocean in the south, and Kebumen-Banyumas plain in the west. This Purworejo plain comprises reworked allu- vial deposits, particularly from Tertiary volcanic rocks of the South Serayu and West Progo Mount- ains, and the Sumbing Quaternary Volcano. In the northern part older reworked material has formed Purworejo alluvial fan in the east and Kutoarjo alluvial fan in the west. Those alluvial fans developed from northeast side of studied area. The central part of Purworejo plain consists of older coastal alluvial deposits which have been covered by recent fluvial deposits that transported by Wawar River in the west, Jali River in the middle, and Bogowonto River in the east. The southern part of Purworejo plain, starting from the Lereng River until present coastal line is composed of younger alluvial coast- al deposits. It is suggested that groundwater resources are abundant under the Purworejo plain, and the young alluvial coastal deposits contain highly potential iron sand and associated minerals. Â